Evaluation de valeur nutritive des issues de cereales: consequences sur l'etablissement de normes alimentaires pour les animaux de trait - Reed, J.D.; Goe, M.R. (1989)
Reviews analytical methods for the determination of the nutritive value of crop residues. Gives example on the accuracy of different methods in determining digestibility and of the factors affecting it. Highlights different management practices for feeding cereal crop residues to draught animals.